Psychosocial functions and consequences of gossip in organizations: or the case of a group of workers in a business area in a service provider company - Moreno Cabezas, Sandra Catalina; Vásquez Ochoa, Andrés Miguel; Gañán Moreno, Anderson; Orejuela Gómez, Johnny Javier (Pensando Psicología, 2020)
Objective. The psychosocial functions and positive and negative consequences of gossip were identified within a group of marketing employees from a service company in Medellin, Colombia. Methodology. It was a qualitative study with a descriptive approach developed as a case study based on semi-structured interviews with 7 employees. Gossip was found to have the psychosocial function of enabling the transmission of information, strengthening the bonds of friendship, and entertainment. Results. The main facilitator of gossip is uncertainty; the main obstacle is censorship; the positive aspect about gossip is that it empowers the transmission of the organizational culture and, paradoxically, it can be an enabler of conflict resolution, as well as a generator of conflicts, misunderstandings, and discomfort. In conclusion, gossip works as an effective mechanism for the exchange of information with evaluative content about absent third parties in a context of trust, allowing the release of emotional states, which prevents the direct expression of violence in organizations.